Sweet Potato Leaf-Based Functional Drinks for Anemia Prevention in Stunting Locus Areas of Kuningan Regency - Jubaedah, Entin; Suratmi, Suratmi; Hermawan, Moh. Hisyam (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Stunting remains a significant public health concern despite a decline in prevalence from 24.4% (2021) to 21.6% (2022), as reported by the Indonesian Nutrition Status Survey (SSGI). One strategy to address stunting is preventing anemia in adolescents. This study examines the effectiveness of a sweet potato leaf-based functional drink in preventing anemia among adolescents in the Nusaherang Health Center, Kuningan Regency, where sweet potato cultivation is abundant. A quasi-experimental pre-test and post-test control design was used, with stratified random sampling to select adolescents aged 10–19 years who met inclusion criteria. Hb levels were measured before and after the intervention. Results showed a median Hb level increase from 11 to 12, with a p-value 0.001, indicating a statistically significant improvement. These findings suggest that sweet potato leaf-based functional drinks are effective in preventing anemia, offering a cost-efficient and accessible intervention for adolescent health.